VLIK from Madrid to Vienna: the Search for a New Political Direction in the Liberation of Lithuania - Banionis, Juozas (Genocidas ir rezistencija, 2013)
The Supreme Committee for the Liberation of Lithuania (Vyriausiasis Lietuvos išlaisvinimo komitetas, VLIK), relying on its right to speak on behalf of the subjugated nation and its belief in the meaning of the Helsinki Accords, emphasised the importance of the Madrid conference for the liberation activities of Lithuania. One more aspect of the Final Act of the Conference on Security and Cooperation in Europe, specifically the territorial integrity principle applicable to the liberation process of the Baltic States, was raised in the Spanish capital. Starting in 1981, the VLIK sought to draw international attention to the situation of Lithuanian dissidents in the Soviet Union and drafted memoranda on the situation in Lithuania. After it was ascertained that there was no possibility to raise the case of Lithuania’s freedom at the United Nations, focus was shifted to the situation evolving in Europe. A permanent VLIK representative for maintaining contacts with the European Parliament (EP) was therefore appointed. In co-operation with the Lithuanian diplomatic service and political organisations, the VLIK operated consistently and saw the passing of an EP resolution on the situation in the Baltic States in 1983. Observing signs of a new political trend in the liberation process of Lithuania, the VLIK sought to ensure that the ‘passive position of non-recognition of the occupation of Lithuania’ would become ‘an active and effective campaign’. To this end, expanding the geographical scope of its political activities, the VLIK established and strengthened its representative offices in North and South America, Australia, and Europe. The earlier strategy of cooperation between Lithuanians in the free world and those in the occupied country remained. Having established its intention to restore the ‘execution of the sovereign powers of Lithuania’, VLIK urged political figures at the Vienna conference to hold ‘a broader campaign in Europe’.
Keywords: Lithuania; soviet occupation; emigree; Lithuanian liberation movement; VLIK